Analisis Valuasi Saham Menggunakan Metode Dividend Discounted Model pada Perusahaan Sub-Sektor Pulp & Kertas - Salsabila Dwi Anggita; Muhammad Umar Mai; Fatmi Hadiani (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Recently, the community has been shocked by a pandemic, namely the Corona Virus (Covid-19) which has an impact on all directions, one of which is the economic sector. The occurrence of global economic uncertainty triggers the Indonesian people to make efforts to maintain their economy. One of them is by investing, especially investing in stocks, especially now that millennials can reach the price of listed share on the IDX. Therefore, the ains of this papper to see the results of the comparison of the intrinsic value of the fair share price with its market price in the pulp & paper sub-sector listed on the IDX in 2016 - 2020 so that it will decide the investment resolve that will be taken by investors whether they are in poor condition. undervalued or overvalued by using the Dividend Discounted Models (DDM) method. The outcome of the analysis in this study obtained that all companies have shares in an overvalued position where the market price is less than the intrinsic value / fair price.